Estimation of residual stress in carbon fibre composite laminate using the contour method - Ahmad, Bilal; Zhang, Xiang; Guo, Hua; Fitzpatrick, Michael E.; Ayre, David (Elsevier, 2026)
Experimental analysis of residual stress in carbon-fibre-reinforced polymer (CFRP) composites is rare owing to the difficulties of determining residual stress accurately in these materials. This can lead to non-conservatism in design and poor understanding of potential failure mechanisms. In this study we have determined the residual stress in a cross-ply CFRP laminate. For the first time, the contour method of residual stress measurement was applied using wire electric-discharge machining (WEDM), the process that is accepted as the best way to ensure an accurate relaxed surface profile is obtained to back calculate the residual stress. A novel incremental linear smoothing approach was introduced for the measured displacement data which gave better approximation than the conventional spline smoothing method used in the standard contour method for metals. Measurements show tensile residual stress in the direction transverse to the fibres with a maximum value of 40 MPa, and compressive residual stress along the fibre direction with a maximum value of –130 MPa. The accuracy of the calculated residual stress was improved by considering the measured thickness of each ply cluster rather than the nominal thickness. The results of modified contour method are compared with an analytical solution based on the classical laminate theory.
Keywords: 40 Engineering; 4016 Materials Engineering; 4001 Aerospace Engineering; Materials; Carbon-fibre-reinforced polymers; Laminate; Residual stress; Contour method